Difficult Diagnosis: Acute Myocarditis or Myocardial Ischemia in an Infant with Thrombophilia? Clinical Case - Oksana A. Vazemiller; Natal’ya S. Ponamareva; David M. Chubko; Ivan Y. Ushakov; Natal’ya Yu. Makarevskaya; Mikhail M. Sharoglazov; Ekaterina V. Basalova; Ekaterina P. Kirillova; Alla B. Salmina; Elena Yu. Emel’yanchik (Вопросы современной педиатрии, 2017)
The article describes the history of a female patient of the first year of life with ischemic heart disease associated with congenital thrombophilia and the development of myocardial infarction. This diagnosis in pediatric practice is casuistry and leads to an adverse outcome more often than in adult patients. The described clinical case draws attention of pediatricians to the alarming symptoms, which allow to suspect thrombophilia in children of the first months of life.